-2+2(5-5v)=-7(v+1)

Simple and best practice solution for -2+2(5-5v)=-7(v+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+2(5-5v)=-7(v+1) equation:



-2+2(5-5v)=-7(v+1)
We move all terms to the left:
-2+2(5-5v)-(-7(v+1))=0
We add all the numbers together, and all the variables
2(-5v+5)-(-7(v+1))-2=0
We multiply parentheses
-10v-(-7(v+1))+10-2=0
We calculate terms in parentheses: -(-7(v+1)), so:
-7(v+1)
We multiply parentheses
-7v-7
Back to the equation:
-(-7v-7)
We add all the numbers together, and all the variables
-10v-(-7v-7)+8=0
We get rid of parentheses
-10v+7v+7+8=0
We add all the numbers together, and all the variables
-3v+15=0
We move all terms containing v to the left, all other terms to the right
-3v=-15
v=-15/-3
v=+5

See similar equations:

| 41=3x-13 | | -14g-18+20g=6g-18 | | 3m-3m=7 | | -5(-8x-5)=-4(8-x) | | 1+2n+3n=6 | | -16-17y+3=14-20y | | j−62=-20 | | ((12/19)x^2)=192/5491 | | X+4x=228 | | -(5a+6)=2(3a+8) | | -5x-6(6-5x)=6(3x+1) | | 19=s−21 | | 10q=-2(-5q-18)+16 | | m+49=57 | | 3x+9-5x=23 | | -14x^2+7x-16=0 | | -8+16n=-2(-8n+4) | | Y2x-6=x-14 | | 5x+20=4x+10=x6 | | (t)=−20+11t | | 2(x-3)+2=-3(x+8) | | -4(2x+3)=2x+6-(8x=2) | | m5=7 | | 15x-24-4x=-76 | | 57+62+43+b=55 | | -5f+12-11f=12-16f | | 4y+3-2y=9+y-3 | | 2(7+3m)=8(1+m) | | 6x-4=x-16 | | -19+2r=6r-5-4r | | -6x+5-x=82 | | -4b-(4b+8)=2(b+6) |

Equations solver categories